Floating Offshore Wind and Carbon Credits in Brazil: A Case Study on Floating Production, Storage and Offloading Unit Decarbonization - Annelys Machado Schetinger; Hugo Barros Bozelli; João Marcelo Teixeira do Amaral; Carolina Coutinho Mendonça de Souza; Amaro Olimpio Pereira; André Guilherme Peixoto Alves; Emanuel Leonardus van Emmerik; Giulia de Jesusda Silva; Pedro Henrique Busin Cambruzzi; Robson Francisco da Silva Dias (Resources)
This study analyzes the economic impacts of integrating floating offshore wind farms with a Floating Production, Storage and Offloading (FPSO) unit to reduce carbon dioxide emissions. The idea is to replace the use of natural gas for power supply with an offshore wind farm, considering the effects of carbon pricing. Results show that wind integration reduces emissions by 23% to 76%, depending on the installed capacity. However, higher wind capacity increases total system costs, initial investment, electricity and operational expenses. The Brazilian carbon credit market adversely impacts existing FPSO units as a result of the compulsory carbon trading costs necessary to mitigate their emissions. In contrast, wind-integrated scenarios benefited from carbon pricing, improving financial indicators such as payback period and Return on Investment. Wind shares of 30% and 70% yielded the best financial results for carbon prices between 10 and 50 United States Dollars per ton, with higher penalties further improving viability. These findings elucidate the significance of carbon pricing in mitigating emissions and enhancing the economic feasibility of offshore wind farms within the context of the Brazilian national FPSO decarbonization strategy.